Implementation of computerised physician order entry (CPOE) and picture archiving and communication systems (PACS) in the NHS: quantitative before and after study. (14th August 2008) - Collin, Simon; Reeves, Barnaby C; Hendy, Jane; Fulop, Naomi; Hutchings, Andrew; Priedane, Eugenia
Abstract : Objective To assess the impact of components of the national programme for information technology (NPfIT) on measures of clinical and operational efficiency. Design Quasi-experimental controlled before and after study using routinely collected patient level data. Setting Four NHS acute hospital trusts in England. Data sources Inpatient admissions and outpatient appointments, 2000-5. Interventions A system for ordering pathology tests and browsing results (computerised physician order entry, CPOE) and a system for requesting radiological examinations and displaying images (picture archiving and communications system, PACS). Main outcome measures Requests per inpatient, outpatient, or day case patient for full blood count, urine culture and urea and electrolytes tests, and plain x ray film, computed tomography, and ultrasonography examinations. Results CPOE was associated with a reduction in the proportion of outpatient appointments at which full blood count (odds ratio 0.25, 95% confidence interval 0.16 to 0.40), urea and electrolytes (0.55, 0.39 to 0.77), and urine culture (0.30, 0.17 to 0.51) tests were ordered, and at which full blood count tests were repeated (0.73, 0.53 to 0.99). Conversely, the same system was associated with an almost fourfold increase in the use of urea and electrolytes tests among day case patients (3.63, 1.66 to 7.94). PACS was associated with a reduction in repeat plain x ray films at outpatient appointments (0.62, 0.44 to 0.88) and a reduction in inpatient computed tomography (0.83, 0.70 to 0.98). Conversely, it was associated with increases in computed tomography requested at outpatient appointments (1.89, 1.26 to 2.84) and computed tomography repeated within 48 hours during an inpatient stay (2.18, 1.52 to 3.14). Conclusions CPOE and PACS were associated with both increases and reductions in tests and examinations. The magnitude of the changes is potentially important with respect to the efficiency of provision of health care. Better information about the impact of modern IT is required to enable healthcare organisations to manage implementation optimally.